2014
DOI: 10.1007/978-3-662-44140-4_8
|View full text |Cite
|
Sign up to set email alerts
|

The Periodic Decomposition Problem

Abstract: Dedicated to Imre Z. Ruzsa on the occasion of his 60 th birthday.Abstract If a function f : R → R can be represented as the sum of n periodic functions as f = f 1 + · · · + f n with f (x + α j ) = f (x) (j = 1, . . . , n), then it also satisfies a corresponding n-order difference equation ∆ α1 . . . ∆ αn f = 0. The periodic decomposition problem asks for the converse implication, which may hold or fail depending on the context (on the system of periods, on the function class in which the problem is considered,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(84 reference statements)
0
0
0
Order By: Relevance
“…More generally, if ∆ T denotes the linear operator defined by ∆ T f (x) = f (x + T ) − f (x), Mortola and R. Peirone [4] have shown that if (Wierdl [5] proved before one implication). This result is extended in [1] and [2] in more general settings. It implies in particular that if, for some integer n ≥ 1, f (x) = x n for all x ∈ R, then f can be expressed as the sum of n + 1 periodic functions, but cannot be written as the sum of n periodic functions.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…More generally, if ∆ T denotes the linear operator defined by ∆ T f (x) = f (x + T ) − f (x), Mortola and R. Peirone [4] have shown that if (Wierdl [5] proved before one implication). This result is extended in [1] and [2] in more general settings. It implies in particular that if, for some integer n ≥ 1, f (x) = x n for all x ∈ R, then f can be expressed as the sum of n + 1 periodic functions, but cannot be written as the sum of n periodic functions.…”
Section: Introductionmentioning
confidence: 65%
“…We will see that it is indeed possible whenever f (x) = x for all x. However, M. Laczkovich and S. G. Révész obtained in [3] that in this case, f 1 and f 2 are not measurable (see also [2]). On the other hand, if, for some n ≥ 2, f (x) = x n for all x ∈ R, the question has a negative answer.…”
Section: Introductionmentioning
confidence: 85%